Surveillance of acute flaccid paralysis in the Marches region (Italy): 1997–2007 - D'Errico, Marcello M (BioMed Central, 2008)
BACKGROUND: The last case of poliomyelitis due to transmission of indigenous wild poliovirus occurred in Italy in 1982, however, it is important to guarantee a high quality surveillance as there is a risk of importation of cases from areas where polio is endemic. Stopping poliovirus transmission is pursued through a combination of high infant immunization coverage and surveillance for wild poliovirus through reporting and laboratory testing of all cases of acute flaccid paralysis (AFP) among children under fifteen years of age. The aim of this study was to describe and to evaluate 11 years of active surveillance in the Marches (Italy) in terms of: incidence, aetiology and clinical manifestation of AFP cases. METHODS: The active Acute Flaccid Paralysis surveillance has been carried out in the Marches region since February 1997 by the Chair of Hygiene which established a regional hospital network. Active surveillance involves 15 hospital centres. RESULTS: In the considered period, 0–15 years population varied between 187,051 in 1997 to 201,625 in 2007, so the number of AFP expected cases is 2 per year. From February 1997 to October 2007, 27 cases were found with rates of 1.0/100,000 in 1997; 2.0/100,000 in 1998; 1.0/100,000 in 1999; 0.5/100,000 in 2000; 2.5/100,000 in 2001; 1.0/100,000 in 2002; 0 in 2003; 0.5/100,000 in 2004; 1.5/100,000 in 2005; 2.0/100,000 in 2006; 1.5/100,000 in 2007. In 29.6% of cases two stool samples were collected in 14 days from the symptoms onset. The 60-days follow-up is available for 23 out of 27 cases reported. In 44.5% of cases the definite diagnosis was Guillain Barrè syndrome. CONCLUSION: In general, the surveillance activity is satisfactory even if in presence of some criticalities in biological samples collection. The continuation of surveillance, in addition to the maintenance of current levels of performance, will tend to a further and more detailed sensitization of all workers involved, in order to obtain spontaneous and prompt reporting, and to achieve the optimal standards recommended by the WHO both in the collection of biological samples and the availability of 60 days follow-up, with the goal of eradicating polio from all countries.